Evaluating the association of serum ferritin and hepatic iron with disease severity in non‐alcoholic fatty liver disease. (27th March 2019) - Buzzetti, Elena; Petta, Salvatore; Manuguerra, Roberta; Luong, Tu Vinh; Cabibi, Daniela; Corradini, Elena; Craxì, Antonio; Pinzani, Massimo; Tsochatzis, Emmanuel; Pietrangelo, Antonello
Abstract: Background & Aims: Hyperferritinemia, with or without increased hepatic iron, represents a common finding in non‐alcoholic fatty liver disease (NAFLD). However, it is unclear whether it reflects hepatic inflammation or true iron‐overload and, in case the latter is confirmed, whether this influences disease progression. We therefore explored the association between serum ferritin, degree and pattern of hepatic iron deposition and liver disease severity in patients with NAFLD. Methods: We selected 468 patients with biopsy‐proven NAFLD from 2 European centres. Iron, hepatic and metabolic parameters were collected at the time of liver biopsy. Iron deposits in hepatocytes and reticuloendothelial cells were assessed and graded. Diagnosis of non‐alcoholic steatohepatitis (NASH) and fibrosis staging were performed. Results: A total of 122 (26%) patients had hyperferritinemia, whereas stainable hepatic iron was found in 116 (25%) patients (38% predominantly in hepatocytes, 20% in reticuloendothelial cells and 42% in both). Subjects with stainable hepatic iron, particularly those with a mixed pattern, had higher serum ferritin and transaminases but only a mixed pattern of iron deposition was among the variables significantly associated with presence of NASH. Serum ferritin was not associated with presence of NASH, however it increased with worsening fibrosis stage (F3 compared to F0‐F1), and significantly decreased in stage F4. Conclusions: A mixed pattern of hepatic iron deposition is associated with the presence of steatohepatitis, while serum ferritin increases with worsening fibrosis up to pre‐cirrhotic stage. In individual NAFLD patients, serum ferritin could be evaluated as part of non‐invasive diagnostic panels but not on its own.